2005
DOI: 10.1309/xmb9-k0j4-1lhl-atay
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the CellaVision DM96 System

Abstract: We evaluated the CellaVision DM96 (CellaVision AB, Lund, Sweden), an automated digital cell morphology and informatics system for peripheral blood smears. Technologists agreed with 82% of the instrument's preclassifications. Correlation coefficients between final results released from the CellaVision and results obtained by direct microscopy were 0.96 (all neutrophils), 0.94 (lymphocytes), 0.88 (segmented neutrophils), 0.73 (eosinophils), 0.69 (bands), and 0.67 (monocytes). After correction for statistically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 10 publications
6
39
0
Order By: Relevance
“…Another study showed that when direct microscopy was used as the reference method against, which the results of the CellaVision ® DM96 were compared, with all discrepant results included in the analysis, the specificity was 82–93% and sensitivity was 25–91%, – which was similar to the results of this study. [4] Finally, another study reported that blood cell and platelet morphology was judged to be adequate; however it was not specific for RBC morphological abnormalities. [11]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that when direct microscopy was used as the reference method against, which the results of the CellaVision ® DM96 were compared, with all discrepant results included in the analysis, the specificity was 82–93% and sensitivity was 25–91%, – which was similar to the results of this study. [4] Finally, another study reported that blood cell and platelet morphology was judged to be adequate; however it was not specific for RBC morphological abnormalities. [11]…”
Section: Discussionmentioning
confidence: 99%
“…[1] Recent advances in laboratory medicine have allowed for automated devices, like the CellaVision ® DM96 (CCS; CellaVision, Lund, Sweden), to screen for specific cell abnormalities at a much more efficient rate than without automation. [234567] Previous evaluations of these types of systems have shown good correlations with the manual differentiation of normal cells. [489]…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have reported a median leukocyte differential count accuracy of 90.3% in comparison to reference manual differentials. [456714] Others have reported a range of accuracy of pre-classification of erythrocyte morphological abnormalities from 65% to 98%, depending on the nature of the abnormality. [16] Still others have evaluated platelet-counting concordance relative to standards, noting a range of correlation coefficients from 0.92 to 0.94.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The CellaVision platforms are among the most thoroughly studied digital hematology platforms in use. Indeed, a review of the literature highlights the rigorous evaluation that the CellaVision system has undergone by multiple groups and from multiple perspectives: Several studies have supported the accuracy and precision of CellaVision for the purposes of the leukocyte differential;[23456789101112131415] others have highlighted the accuracy and precision of CellaVision in the analysis of red cell parameters;[345111316] others still have validated CellaVision for use in platelet counting and morphological assessment. [3111317] In reviewing the literature, only a single publication could be identified pertaining to the evaluation of digitized slide analysis for the purpose of reticulocyte counting;[18] however, no CellaVision-specific data was identified.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises: an automated microscope that scans the blood smear; a digital camera that captures images of all the cellular and particulate material on the slide; and a computer that classifies each image by means of complex algorithms. It has been demonstrated to have good performance characteristics in developed countries, 5,6,7,8,9 but to date has not been evaluated in Africa, where the spectrum of pathology encountered is very different. Most notable in sub-Saharan Africa is the extremely high prevalence of HIV infection.…”
Section: Introductionmentioning
confidence: 99%